Penerapan Tehnologi Tepat Guna pada Agrowisata Sangkareang di Desa Tetebatu Selatan, Lombok Timur - Murianto, Murianto (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Politeknik Negeri Banyuwangi, 2025)
This community service activity aims to implement appropriate technology (TTG) to support the development of Sangkareang Agrotourism in South Tetebatu Village, East Lombok Regency. Sangkareang Agrotourism has significant potential in horticulture and ecotourism, but many challenges and constraints remain in terms of management and production efficiency. Through the application of appropriate technology, including organic fertilizer processing equipment, drip irrigation systems, and the use of greenhouses, this activity is expected to increase productivity, time efficiency, and the quality of agricultural products, which will become a tourist attraction in South Tetebatu Village. The implementation method included a participatory approach, training, equipment demonstrations, and technical assistance to farmer groups and agrotourism managers. The results of the activity demonstrated that the application of appropriate technology, such as greenhouses, can improve community understanding and skills in sustainable agricultural management, reduce dependence on chemical fertilizers and pesticides, which are highly hazardous to health, and strengthen the competitiveness of Sangkareang Agrotourism as an educational and environmentally friendly tourist destination in East Lombok Regency. Green House appropriate technology not only provides economic benefits for the community but also supports the realization of sustainable tourism based on local wisdom in South Tetebatu Village, East Lombok.